Treatment and prophylaxis of moderate and severe bronchopulmonary dysplasia in premature neonates - A.V. Bolonska; O.Yu. Sorokina (Medičnì Perspektivi)
Bronchopulmonary dysplasia in premature neonates leads to physical and mental developmental disorders and behavioral problems and associated with frequent rehospitalizations and long hospital stay. Study objective: to study the predictors of bronchopulmonary dysplasia development in premature neonates in structure of intensive care. Study design: A retrospective cohort analysis was performed in 127 children recruited from two NICU of Dnipro between January 2016 to March 2020. Inclusion criteria: preterm neonates 28-32 gestation weeks with respiratory distress syndrome (RDS). Results demonstrated that every day of mechanical ventilation, supplemental oxygen with FiO2 more than 30% and cardiac drugs usage increased risk of bronchopulmonary dysplasia development by 15-20%. In conclusion, finding out predictors of bronchopulmonary dysplasia helps to improve  and prudently use usual treatment regimens in premature neonates and decrease the frequency of moderate and severe bronchopulmonary dysplasia.